Speech text of ACIS postgraduate open day for Middle Eastern universities / Prof. Datuk Ts. Dr. Roziah Mohd Janor - Mohd Janor, Roziah (2023)
Congratulations to the organising committee from the Academy of Contemporary Islamic Studies (ACIS) UiTM, under the leadership of the Dean, Associate Professor Dr Mohd Afandi Mat Rani, for successfully initiating this international collaboration.